Reinventing Konsep Muhkam-Mutasyābih dan Pengembangannya dalam Tafsir al-Qur’an Kontekstual - Ahmad Syaifuddin Amin (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
Discourse of Muhkām-Mutasyābih which has been discussed in the classical literatures of ulūm al-Qur‘ān was getting worse because of some shift meanings especially specialization that limits muhkām-mutasyābih discussion on the teological verses of the Quran. The lack of discussion and elaboration on muhkam-mutasyābih in interpreting Quran worsens this situation. The effort to reframe this specialization among classical scholars and the reinventing concept of muhkam-mutasyābih could open prospective ways to elaborate this discourse and other approapches in Quranic exegesis. By inventarizing some concepts of muhkam-mutasyābih initiated by Islamic Scholars and considering them by interpretation rules, this article concludes that some muhkam-mutasyābih concepts of the scholars should be considered and elaborated in interpreting Quran. As a consequence of diversable interpretation of Quran, This various concepts of muhkam-mutasyābih should be expanded to the interpretation of the Quran for constructing contextual interpretation of the Quran keeping the balance of textual values and answering human needs of Quranic Solution for their problems.